Real world Windows 8 app development with JavaScript : create great Windows Store apps - Moemeka, Edward; Moemeka, Elizabeth (Expert's voice in Windows 8., 2013)
Real World Windows 8 App Development with JavaScript offers you practical advice and hard-earned insights that will help you create and publish apps to a worldwide market. Led by authors with deep Windows 8 app development experience, youll learn how to make the most of Microsofts APIs for hooking into Windows 8 on all devices, including the core ideas of promises and the asynchronous programming model. Youll also discover such important tips as how to Adhere to Windows 8 guidelines for successful app acceptance Extend the appeal of your app with media, contracts, charms, and user notifications Capture and work with media, including the ability to play video wirelessly to a television Manage background processing and file transfers Gain visibility for your app and add monetization optionsReal World Windows 8 App Development with JavaScript features real-world examples that emphasize the use of JavaScript and HTML 5 and that also adhere to the stylistic guidelines Microsoft has put in place to maintain a consistent look and feel for all applications on this platform. Get the low-down from authors with experience from the front lines of Windows 8 app development. Theory is all well and good, but when it comes down to it, you cant beat practical advice from people whove been there and done it! Youll come away from this book with all the tools, ideas, and inspiration you need to create successful Windows 8 JavaScript apps.